2010
DOI: 10.1017/s1047951110001733
|View full text |Cite
|
Sign up to set email alerts
|

Microembolic signals measured by transcranial Doppler during transcatheter closure of atrial septal defect using the Amplatzer septal occluder

Abstract: Transcatheter closure of atrial septal defect using the Amplatzer septal occluder produces microemboli, especially during device placement. To minimise the risk of systemic embolism, we must decrease the time for device manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 12 publications
0
15
3
Order By: Relevance
“…[84][85][86] An emerging area for the use of transcranial Doppler sonography is perioperatively in children with congenital heart disease. [87][88][89][90][91][92] Cheng et al 90 measured flow velocities intraoperatively through 18 hours after cardiopulmonary bypass in 100 infants with congenital cardiac disease who underwent biventricular repair.…”
Section: Other Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[84][85][86] An emerging area for the use of transcranial Doppler sonography is perioperatively in children with congenital heart disease. [87][88][89][90][91][92] Cheng et al 90 measured flow velocities intraoperatively through 18 hours after cardiopulmonary bypass in 100 infants with congenital cardiac disease who underwent biventricular repair.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Additionally, recent studies have found that nearly all children undergoing transcatheter closure of atrial septal defects had microembolic signals during the procedure. 91,92 In 24 chil- . Transcranial Doppler waveform from the right middle cerebral artery in an 11-month-old child with acute liver failure and right intraparenchymal hemorrhage who met clinical criteria for brain death.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Despite the broad range in underlying cardiac anatomy and physiology and procedures performed, pediatric studies have reported HITS occurring in “bursts” and clusters, often in association with a septal defect and/or right to left shunt . Maneuvers during catheterization for closure of atrial septal defects, namely, sheath placement, balloon sizing, and device placement, have been associated with HITS in children and young adults . Although not recorded for our study, other procedures in the catheterization laboratory, such as blood sampling and injection of drugs, fluids, and contrast agents, have also been reported to produce HITS .…”
Section: Discussionmentioning
confidence: 72%
“…27 Maneuvers during catheterization for closure of atrial septal defects, namely, sheath placement, balloon sizing, and device placement, have been associated with HITS in children and young adults. 23,28 Although not recorded for our study, other procedures in the catheterization laboratory, such as blood sampling and injection of drugs, fluids, and contrast agents, have also been reported to produce HITS. 26,29 Published studies vary in the TCD device and associated software used, Doppler settings, definition of HITS, calculation of HITS (manual and/or automated), and number of cerebral arteries insonated (Table 3).…”
Section: Discussionmentioning
confidence: 92%
“…TCD [4][5][6][7][8] has been widely used in clinical screening for clinical monitoring in recent years due to the characteristics of economy, non-invasiveness, repeatable check and so on. CDUS, [9][10][11] as one of the most popular vascular ultrasound techniques, has an irreplaceable advantage in the evaluation of the vascular wall, plaque morphology and stenosis of the extra cranial segment.…”
mentioning
confidence: 99%